STAKEHOLDER PERSPECTIVES ON THE SATISFACTION OF VILLAGE FINANCIAL GOVERNANCE IN SERANG REGENCY - Prasetyo, Eko; Hunainah, Hunainah; Maulana, Rachmat (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study analyzes stakeholder satisfaction towards village financial governance in Serang Regency. A quantitative approach was employed, involving a survey of 400 respondents from various villages selected purposively based on Article 16 of the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration’s Regulation No. 21 of 2020. The data were collected using questionnaires with a Guttman scale. The research findings indicate that 59% of respondents are dissatisfied with village financial management, while 41% express satisfaction. The study highlights that public satisfaction towards financial governance is influenced by information transparency, participation in decision-making, program distribution, and direct benefits received. Male respondents report higher satisfaction than females due to more intensive involvement in village activities. Active participation enhances expectations and overall satisfaction among residents. However, disparities in benefit distribution of programs remain a challenge. To improve satisfaction, village governments must enhance transparency, increase community participation, and ensure a more equitable and impactful distribution of programs. The implications of this study emphasize the importance of improving village financial governance by strengthening transparency, fostering community engagement, ensuring fair program distribution, and enhancing community support to increase stakeholder satisfaction in financial management.